Flower, seed, and fruit development in three Tunisian species of Polygonum: Implications for their taxonomy and evolution of distyly in Polygonaceae. - Maher Mahmoudi; Fayçal Boughalleb; Giuseppe Pellegrino; Raoudha Abdellaoui; Nizar Nasri (PLoS ONE)
Polygonum is the largest genus of Polygonaceae and 5 species are reported in Tunisia. In order to characterized flower, seed, and fruit development in Polygonum, flower and fruit of Polygonium equisetiforme (var. graecum and peyerinhoffi), P. aviculare and P. maritimum, collected from Tunisia, were examined. Flowers are composed of five oblong tepals. P. equisetiforme and P. aviculare have whitish-pink distylous flowers with dimorphism of style, filament and anther height, pollen diameter and stigma size. In contrast, P. maritimum shows white homostylous flowers. The floral vasculature showed that the tepals are inserted in one whorl and their traces arise independently in 3+2 manner. The eight stamens are arranged in a 5+3 manner and the staminal bundles arise independently in the two whorls. The epidermis and endothecium cells width were higher in P. maritimum and the lowest endothecium width was observed in P. aviculare. Polygonum aviculare and P. equisetiforme showed circular pollen with shallow colpi and trilobite pollen shape with deep colpi, while P. maritimum rarely showed shallow colpi. The ovule is anatropous with basal placentation in P. equisetiforme and P. aviculare and apical placentation in P. maritimum. The young seed coat was formed by an endotesta with thick-walled cells, a mesotesta and exotesta with thin-walled cells and a tegmen composed of radially elongated cells. The fruits of the studied species are trigonous with ovate-lanceolate shape. In P. aviculare, the exocarp is thicker compared to the two other species, in P. equisetiforme, the mature exocarp consists of smaller rectangular cells with narrow cavities, and in P. maritimum showed a thinner exocarpIn conclusion, P. equisetiforme and P. aviculare are a typically distylous species from the morphological point of view and we discussed the significance of heterostyly in Polygonaceae. From this first morpho-anatomical study of Polygonum species in North Africa, we can conclude mainly that there is no significant difference between P. equisetiforme var. graecum and var. peyerinhoffi supporting a taxonomic grouping of these two varieties.